AYAT SUCI LENYEPANEUN AND SOCIAL CRITIQUES: Moh. E. Hasim’s Critiques of the Political Policy of the New Order (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
One of the main objectives of the tafsīr (Quranic interpretation) is to explain its Quranic contents to readers. In fact, tafsīr also demonstrates an interaction between writers of tafsīr and their socio-context where they lives. In Sundanese region, Moh. E. Hasim also criticised the New Order’s policies when he wrote his tafsīr called Ayat Suci Lenyepaneun. What are his critiques? How did he make critiques when at the same time he was writing the tafsīr? How was his critique’s position among socio-discourses that appeared in the Muslim world? Through the discourse-analysis approach, this study argues that Hasim’s comments on the New Order’s policies in his Lenyepaneun tafsīr demonstrate a dialectical process of the interpreter (writer) with the socio-political context, which he faced. The texts’ critiques of Hasim to the issue of gambling (Porkas and SDSB) and banning of veil demonstrated Hasim’s challenge to the government’s hegemony, which was very repressive. Hasim has successfully combined varieties of ‘horizons’, one being himself as a writer, the socio-political horizon and the horizon of the readers. Hasim’s tafsīr has not only displayed the socio-political situation of the society at that time but also became his tool to deliver his critiques.